THE INFLUENCE OF CONTENT ORIGIN ON TRUST AND ENGAGEMENT: A COMPARATIVE STUDY OF AIGENERATED AND HUMAN-GENERATED CONTENT FOR INDONESIAN COMMUNICATION AND INFORMATION INDUSTRY - Ibnusina Wiyono, Muhamad
This thesis examines the differential impacts of AI-generated and humangenerated content on customer trust and brand engagement within Indonesia's communication and information industry. By focusing solely on quantitative analyses, the study measures how perceptions of trust and engagement vary depending on the source of content creation. The research employs a structured survey methodology, gathering responses from 240 participants to quantitatively assess their reactions to both types of content across established dimensions of trust—competence, integrity, and benevolence—and engagement—cognitive processing, emotional affection, and behavioral activation.